Exploring the influence of organic species on pre- and post-nucleation calcium carbonate - Raiteri, Paolo; Demichelis, Raffaella; Gale, Julian; Kellermeier, M.; Gebauer, D.; Quigley, D.; Wright, L.; Walsh, T. (Royal Society of Chemistry, 2012)
Organic additives are well known to influence the nucleation and growth of minerals. A combination of experimental and theoretical methods has been used to probe how three simple additives, containing varying numbers of carboxylate groups, influence the early stages of the growth of calcium carbonate. Computationally, the free energy landscape has been examined for each additive binding to Ca2+, the calcium carbonate ion pair, the surface of an amorphous calcium carbonate nanoparticle, and the basal plane of calcite. The different influence of the three organic ligands on the early stages of growth of calcium carbonate observed experimentally can be rationalised in terms of the degree of association of each anion with the species present prior to, and immediately after nucleation.